Unveiling the Potency of Coriandrum sativum as Repellent for Antimalarial: In silico Study - Gabriella Chandrakirana Krisnamurti; Dewi Ratih Tirto Sari (Proceeding International Conference on Religion, Science and Education, 2023)
This study identified the potency of 2-Decenoic acid and Cyclododecanol from C. sativum as a repellent agent for antimalarial with in silico approach. The 3D structures of 2-Decenoic (CID5282724) and Cyclododecanol (CID15595) were downloaded from the PubChem database. Bioactive compounds were docked with macromolecule AgamOBP-1 (3N7H) from the PDB database using Molegro Virtual Docker 5. Docking results were visualized and analyzed by Pymol and Discovery studio 4.1. Visualization was done as 2D and 3D form. The result showed that 2-decenoic acid and cyclododecanol were performed binding to the active sites odorant binding protein of Anopheles mosquito. Several residues of AgamOBP-1 protein was identified both of cyclododecanol and 2-decenoic acid of C. sativum, which were LEU96, MET89, HIS77, ALA88, and LEU76. Those residues has a pivotal region of AgamOBP-1 protein. Besides that, those residues also found as DEET active sites, indicating the same mechanism action of cyclododecanol and 2-decenoic acid. The inhibition of AgamOBP-1 prevent mosquitoes from taking blood from the host. In summary, in silico study suggested that cyclododecanol and 2-decenoic acid of C. sativum were potentially preventing malaria by AgamOBP1 inhibition. Further study needed to establish the plant product as an oil for an antimalarial agent.